The Influence of Training and Use of Information Technology on Employee Performance with Employability as an Intervening Variable - Andi Resqi Amelia (Scientium Management Review, 2022)
Training is a series of individual activities in systematically increasing skills and knowledge so that they are able to have professional performance in their field. Information Technology is a set of tools that help you work with information and perform tasks related to information processing. The reasons for the researchers to take to find out the effect of training and the use of information technology on employee performance with work ability in employees of PT. Wira Eka Persadatama Bone. Respondents in this study amounted to 49 marketing employees with details of men and women. Data collection techniques using questionnaires with descriptive quantitative methods. The analysis phase in this study begins with the research instrument, namely by collecting data and processing the data obtained in the Analysis Phase in this study beginning with research instruments, namely by collecting data and processing data obtained through observation, questionnaires, interviews, and documentation by giving the weight of each statement based on a Likert scale, and do the validity test and reliability test.. The regression test used is multiple regression. In its implementation, data processing was carried out with the help of the SPSS program. To test the effect of mediation (intervening) the path analysis method was used. The results of the research show (1) training has an effect on work ability; (2) the use of information technology affects work ability; (3) training has an effect on employee performance; (4) the use of information technology affects employee performance; (5) work ability affects employee performance.